Recent design studies for the novel momentum spectrometer NoMoS. (December 2020) - Moser, D; Khalid, W; Jiglau, R; Soldner, T; Valentan, M; Zmeskal, J; Konrad, G
Abstract: NoMoS is a novel momentum spectrometer with which we aim to measure the spectra of the charged neutron beta decay products with high precision. The shape of the proton and electron spectra can inter alia be used for the determination of the electron-antineutrino correlation coefficient a and the Fierz interference term b, respectively. These observables can in turn be used to test the Standard Model of Particle Physics and to search for extensions thereof. NoMoS utilizes the R × B drift effect present in curved magnetic fields, which disperses charged particles according to their momentum. In this paper, we report on selected recent investigations that were conducted with regard to the magnet design and the detection system.